Handling Cases of Child Sexual Abuse from an Islamic Legal Perspective (Case Study at DP3A Banda Aceh) - Nada Adzkia; Fakhrurrazi M. Yunus; Aulil Amri (QURU’: Journal of Family Law and Culture, 2025)
The protection of children is a fundamental aspect of Islamic teachings, especially in terms of sexual violence that touches on issues of morality, dignity, and humanity. Islam strictly prohibits adultery and actions that lead to it, including sexual abuse of children. A severe issue that persists in Indonesia is sexual violence against minors, including in Banda Aceh City, with various forms ranging from harassment to rape. Children who should receive protection actually become victims in their immediate environment, such as family, neighbours, and even peers. Through a case study at DP3A Banda Aceh, this study seeks to examine how situations of sexual abuse against children are handled from the standpoint of Islamic law. Data were gathered through observations, interviews, and literature reviews from books, journals, rules and regulations, and Qur'anic verses using a legal sociological method and a normative-empirical juridical approach. The study was descriptive and qualitative in nature. According to the study's findings, DP3A Banda Aceh plays a significant role in providing social recovery, legal support, and psychological support to victims of sexual assault against minors. However, this effort still faces various challenges, such as minimal reporting of cases, social stigma against victims, and limited human resources and coordination between institutions. In the context of Islamic law in Aceh, handling this case requires a comprehensive approach, integrating religious values, local customs and the national legal system to give children, the country's future generation, the best possible protection.